INTERPRETASI MAKNA “AL-MA’ṢIYYAH” DALAM SYARAH HADIS TENTANG FLUKTUASI IMAN (STUDI APLIKASI TEORI SEMIOTIKA CHARLES SANDERS PEIRCE) - Dadi Nurhaedi; Muhammad Alfreda Daib Insan Labib (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
This study examines the interpretation of the meaning of "al-ma’ṣiyyah" within the hadith commentary text "al-īmān yazīd wa yanquṣ, yazīd bi al-ṭō’ah wa yanquṣ bi al-ma’ṣiyyah" using Charles Sanders Peirce’s semiotic theory. Generally, the term "al-ma’ṣiyyah" is interpreted as the act of violating a command; in the context of Islamic studies, the command violated is specifically that of Allah. However, when "al-ma’ṣiyyah" is interpreted using a different approach—specifically Charles Sanders Peirce’s semiotic theory—its meaning undergoes a shift. This research employs a qualitative method, utilizing the Kutub al-Tis’ah and their commentaries (syarah) as the primary sources for the hadith, and the Collected Papers of Charles Sanders Peirce as the primary reference for the semiotic theory. The discussion in this study covers: 1) The commentary on the hadith regarding the fluctuation of faith; 2) The interpretation of the meaning of maksiat within the context of faith fluctuation; and 3) The hadith regarding the loss of one’s faith. The results indicate that: 1) The text "al-īmān yazīd wa yanquṣ, yazīd bi al-ṭō’ah wa yanquṣ bi al-ma’ṣiyyah" serves as a commentary on the hadith concerning the many branches of faith; 2) The meaning of maksiat in this commentary shifts from "violating a command" to "abandoning sunnah (recommended) acts"; and 3) The hadith regarding the loss of faith explains that a believer who commits adultery, becomes intoxicated, or steals is not considered to possess faith at the moment these acts are committed.